Serious game for cognitive assessment. Validation of a psychometric embedded test - Jorge Quimbaya; Alejandra Herrera; Cesar Mejia (International Journal of Serious Games, 2024)
The evaluation of performance in serious video games is crucial when it comes to providing empirical evidence of the effectiveness of this type of educational tools. In turn, the design of psychometric tests demands specific procedures aimed at estimating validity levels. This paper presents the validation process of a psychometric test embedded in a video game, for the assessment of executive functions, understood as a set of cognitive processes associated with the functioning of the frontal lobes, including planning, inhibition, flexibility and monitoring. The sample consisted of 171 participants aged between 5 and 12 years (Mean=8.27; SD=1.589), students at elementary school. The analyses performed included Cronbach's Alpha and McDonald's Omega internal consistency indexes and an Exploratory Factor Analysis. The results indicate good levels of reliability and excellent fit indices for a two-factor model